Food service safety and hygiene factors: a longitudinal study on the Brazilian consumer perception - Carvalho, Natália Caldeira de; Silva, Clarisse Lolli e; Liboredo, Juliana Costa (Frontiers in Nutrition, 2024)
The objective of this study was to investigate the perceptions and attitudes of consumers toward food service safety and hygiene when purchasing ready-to-eat food. Data were collected at three time points: before (T0) and during the COVID-19 pandemic (T1 and T2). Among the 333 participants, 45.9% reported fear of contracting COVID-19 when purchasing off-site meals, and 78.4% for on-site meals in T1, compared to 21.0% and 52.0% in T2, respectively (p<0.001). Hygiene and cleanliness of the establishment became less important for participants when selecting food services throughout the pandemic (T0: 42.6%; T1: 41.1%; T2: 0.0%) (p<0.01). Security protocols during off-site and on-site purchases were considered important by more participants in T1 (47.7% and 27.6%, respectively) than in T0 (28.8% and 9.0%, respectively), with a decrease in T2 (0% and 16.5%, respectively) (p<0.01). Regarding food delivery services, concerns about hygiene decreased in T1 (44%) compared to T0 (63.7%) but increased again in T2 (76%) (p<0.01). Precautions with the food packaging was less prevalent at least during one point in the pandemic compared to T0 (p<0.01), while heating food before consumption was more common at the onset of the pandemic (T1) but declined by T2 (p<0.01). Furthermore, the use of cash decreased while contactless payment methods increased during the pandemic. In conclusion, different phases of the COVID-19 pandemic significantly influenced consumer behavior and attitudes toward purchasing ready-to-eat food.